PENGARUH PENGALAMAN KERJA, KETERAMPILAN KERJA,DISIPLIN KERJA, MOTIVASI KERJA, INSENTIF DAN BEBANKERJA TERHADAP PRESTASI KERJA PEGAWAI PADA BAGIANPENGADAAN BARANG/JASA SEKRETARIAT DAERAHKABUPATEN LAHAT - Darliansyah; Marko Ilpiyanto; Delvina Yulanda (Ekonomika, 2026)
The author's research aimed to determine and analyze theinfluence of work experience, work skills, work discipline, workmotivation, incentives, and workload, both individually andcollectively, on employee performance in the Goods/ServicesProcurement Section of the Lahat Regency Regional Secretariat.The research method used in this study was quantitative, using aquestionnaire distributed to respondents. Data quality was testedusing validity, reliability, and normality tests. The analysis useddescriptive and inferential analyses using statistical calculationsusing multiple regression formulas, partial and simultaneoustests, and coefficients of determination. The results showed thatwork experience, work skills, work discipline, work motivation,incentives, and workload have a positive effect, both individuallyand collectively, on employee performance in the Goods/ServicesProcurement Section of the Lahat Regency Regional Secretariat.